TEACHERS’ BELIEFS ABOUT MATHEMATICAL PROBLEM SOLVING IN ELEMENTARY SCHOOLS : A CASE STUDY IN NUNUKAN REGENCY - Irianto Aras; Turmudi; Tatang Herman (Universitas Majalengka, 2025)
This study aims to describe the beliefs of fifth-grade elementary school teachers and students regarding mathematical problem solving, as well as their approaches to teaching and learning problem-solving activities. The research employed a qualitative descriptive method, focusing on the alignment between teachers’ and students’ perceptions of problem solving within an authentic classroom context.The participants consisted of three teachers from different elementary schools in Nunukan Regency, North Kalimantan, and six students identified by the teachers three categorized as successful and three as less successful in solving mathematical problems. Data were collected through semi-structured interviews and documentation, using an interview guide developed to explore teachers’ beliefs and students’ problem-solving strategies. The validity of data was ensured through source triangulation and member checking. Data were analyzed using Miles and Huberman’s (1992) interactive model, which includes stages of data reduction, data display, and conclusion drawing. The findings revealed three main points: (1) teachers generally associated students’ problem-solving success with innate ability, while students attributed success to effort and persistence; (2) both teachers and students shared a narrow understanding of problem solving, viewing it mainly as procedural computation rather than reasoning or exploration; and (3) teachers assessed students’ success primarily based on accuracy in calculation, resulting in classroom practices that emphasized procedures over conceptual understanding.In conclusion, the study highlights the need to strengthen teachers’ pedagogical beliefs and promote reasoning-oriented instruction in mathematics classrooms. However, the limited number of participants restricts the generalizability of the findings. Future studies with larger samples and classroom observations are recommended to validate and expand these results.